Metabolic adaptation to cancer growth: From the cell to the organism. Issue 2 (28th January 2015) - Escoté, Xavier; Fajas, Lluís
Abstract: Tumour cells proliferate much faster than normal cells; nearly all anticancer treatments are toxic to both cell types, limiting their efficacy. The altered metabolism resulting from cellular transformation and cancer progression supports cellular proliferation and survival, but leaves cancer cells dependent on a continuous supply of energy and nutrients. Hence, many metabolic enzymes have become targets for new cancer therapies. In addition to its well-described roles in cell-cycle progression and cancer, the cyclin/CDK–pRB–E2F1 pathway contributes to lipid synthesis, glucose production, insulin secretion, and glycolytic metabolism, with strong effects on overall metabolism. Notably, these cell-cycle regulators trigger the adaptive "metabolic switch" that underlies proliferation.